Carbon nanotubes: a suitable material for catalytic wet peroxide oxidation of organic pollutants? - Ribeiro, Rui (2012)
Carbon materials, such as activated carbons (AC), graphite and activated carbon xerogels, have been explored as metal-free catalysts for the catalytic wet peroxide oxidation (CWPO) of bio-refractory organic compounds, such as azo dyes and phenolic compounds [1-3]. At the same time, the application of carbon nanomaterials in catalysis, such as carbon nanotubes (CNT), has grown exponentially [4]. In the present work, commercial multiwalled carbon nanotubes (MWNT) were used in the CWPO of 2-nitrophenol and its activity compared to a commercial AC, used as received and after chemical modifications.